Pre-treatment clinical study of rhinosinusitis impact on the quality of life among patients having both external nasal deformity and deviated nasal septum - M. S., Sudhakar Rao; N., Vijaya T.; ., Bipinkumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Sino-nasal disease often gives an experience of impacting quality of life significantly, more so among chronic cases. Hence a self-perceived disease specific impact viz rhinosinusitis disability index (RSDI) which is a validated reliable measure of quality of life is being studied. Methods: A prospective study conducted on patients, attending department of ENT on out and or in-patient basis who are diagnosed to have rhinosinusitis with external nasal deformity and deviated nasal septum (DNS) were selected on simple random basis for this study between July 2018 to November 2019. This study group subjected for answering standard questionnaire of RSDI proforma before treatment. Data statistically analyzed using IBM SPSS version 22. Results: Among the statistically calculated ‘n' (40) patients of this study, 23 were male (57.5%) and 17 were female (42.5%) patients of the age between 15-45 years. In our study, majority of patients (n=23) had simple type DNS (57.5%), followed by obstructive type 37.5% (n=15) and impacted type 5% (n=2) and majority of patients showed type I (50%) external nasal deformity followed by type V (25%). In our study, 11 patients were diagnosed with acute rhinosinusitis, 15 patients with chronic rhinosinusitis without nasal polyps (CRSsNP) and 14 patients with chronic rhinosinusitis with nasal polyps (CRSwNP). The physical, functional and emotional domains showed no statistical significance with respect to external nasal deformity and DNS. However, disease factor had statistically significant impact (p<0.05) on the quality of life among rhinosinusitis patients with mean scores of 13.7, 19.42, and 10.80. Conclusions: In rhinosinusitis patients, the disease affects the quality of life in terms of physical, functional and emotional domains, but not by the external nasal deformity and or DNS associated.